Optimizing Moodle E-Learning Page Features to Enhance Student Achievement in Business Economics - Raidil Fitran; Soeprijanto Soeprijanto; Muksin Muksin (Journal of Pedagogi, 2025)
This study investigates how optimizing Moodle e-learning features can enhance student achievement in Business Economics courses. Grounded in constructivist learning theories and empirical research on Learning Management Systems, the investigation addresses the growing need for effective, technology-driven instructional strategies. A quasi-experimental research design was employed across one academic semester, involving undergraduate students enrolled in a Business Economics course at a public university. Participants were divided into two groups: one that accessed a standard Moodle environment and another that engaged with enhanced Moodle features, including adaptive release of content, personalized feedback tools, and gamified assessments. Data were collected through pre- and post-course tests, platform usage logs, and student perception surveys. Statistical analyses, including t-tests and multiple regression, indicated that students using the optimized Moodle platform demonstrated significantly higher achievement scores and engagement levels than those in the control group. Correlation results further revealed that interactive quizzes and targeted feedback strongly influenced student performance. Qualitative feedback underscored the benefits of gamified elements and user-friendly navigation in fostering deeper learning and motivation. These findings reinforce the vital role of thoughtfully tailored LMS interventions in improving learning outcomes, particularly within complex disciplines like Business Economics. The study concludes by discussing implications for educators, administrators, and platform developers seeking to maximize the pedagogical potential of e-learning systems. Future research should explore longitudinal effects, larger sample sizes, and cross-institutional validations to further refine and generalize these insights